Effects of yeast’s weight and fermentation time to percent yield of bioethanol from peatland - Ahmad Roni, Kiagus; Hastarina, Merisha; Herawati, Netty (International Journal of Engineering and Technology, 2019)
Renewable energy development in Indonesia is one of the government’s programs to reduce carbon dioxide emission and dependence to fossil fuel. Bioethanol is an alternative energy that can be developed to replace solar fuel. Peat is a source of bio-ethanol which is very potential because of its abundant source in Indonesia. This research investigated the lifecycle of bio-ethanol from peat, resulting in carbon dioxide emission reduction and energy net. Fermentation method was used to produce bio-ethanol from peat. In the fermentation, yeast was used and the fermentation temperature was from 200C to 400C. The products were analyzed by a gas chromatograph (GC). The results showed that at the 10th day, the bioethanol production was the highest. This research also concerns to the side effects of by-products from bioethanol production. The use of by-products may improve the environmental performance and bioethanol energy until 30-70%. This research showed that bioethanol (from peat) development in Indonesia is much better compared to other countries.